The Iron Cage Revisited: Institutional Isomorphism and Collective Rationality in Organizational Fields - DiMaggio, Paul J.; Powell, Walter W. (American Sociological Review, 1983)
Instead of examining why organizations are dissimilar, this study explores why organizations tend to be increasingly and inevitably homogenous in their forms and practices. Organizations in a similar line of work are structured into an organizational field by powerful forces that lead them to become similar. Rather than the causes of rationalization and bureaucratization suggested by Max Weber, including competition and the need for efficiency, institutional similarity is due to the structuration of organizational fields, a process caused largely by the state and the professions, which are the great rationalizers of the late 20th century. In highly structured organizational fields, rational efforts of individuals aggregately lead to structural, cultural, and output homogeneity. Homogenization is best captured by the concept of isomorphism, the process whereby one element in a population resembles others that confront the same environmental conditions. The two types of isomorphism are competitive and institutional. Three processes lead to organizational similarity: (1) coercive isomorphism stemming from political influence and the problem of legitimacy; (2) mimetic isomorphism resulting from uniform responses to uncertainty; and (3) normative isomorphism associated with professionalism. While these isomorphic processes improve organizational transactions, they do not necessarily increase internal efficiency. Twelve hypotheses are offered for further research about which organizational fields will be most homogenous. These hypotheses relate the impact of resource centralization and dependency, goal ambiguity and technical uncertainty, and professionalism and structuration on isomorphic change. Finally, useful implications of the study for theories of organizations and social change are offered. (TNM)